The principle of equal treatment in temporary employment - Strupp, Liliana (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The principle of equal treatment of temporary workers is derived from the EU Directive on temporary work. The implementation of this principle in the Polish legal system is guaranteed both by general provisions of the labour law relating to equal treatment and non-discrimination of employees, as well as the provisions of the Act of July 9, 2003 on Employment of Temporary Workers, in particular Art. 15 sec. 1 of this act. The obligation of equal treatment applies to temporary employees assigned to perform work for the user employer and employees directly employed by this employer in the same or similar job position, and concerns two areas: “working conditions” and “other employment conditions”. These two terms have not been explicitly defined in the Polish legal system, while their correct definition and interpretation constitute the basis for the proper understanding and implementation of this principle.